Qualitative Interview Questions: Guidance for Novice Researchers - Roberts, Rosanne (Qualitative report, 2020)
This article, aimed at the novice researcher, is written to address the increased need to develop research protocols or interview guides to meet the requirements set by IRBs and human subjects review committees. When data collection involves conducting qualitative interviews, the instruments include the researcher and the interview questions. The value of the data collected during a qualitative interview depends on the competence of the researcher and the strength of the interview questions. For this reason, it is important to ensure that the interview questions used by novice researchers are appropriate and capable of supporting their efforts to reach their goal of acquiring a detailed answer to the research question. This article expands upon the ideas presented by various authors about the topic of developing robust qualitative interview questions. It provides guidelines that can be used to develop an interview guide that adds structure to the interview process, as well as provides transparency of methods to human subjects review committees and IRBs, while at the same time allows flexibility within the interview process. Various types of interview questions are described and working examples are included.